A numerical investigation on twin elliptic jet-in-crossflow phenomenon - Tan, Kelvin Wei Ming (Nanyang Technological University, 2021)
Both elliptic single jet-in-crossflow (SJICF) and twin jet-in-crossflow (TJICF) are variations of the extensively studied circular SJICF. However, limited studies have been conducted on both cases, especially for the TJICF variant; where the effect of jet geometry on this configuration remains a mystery. The purpose of this study is to provide further insights on the effects of jet geometry, in this case, a low aspect ratio elliptic jet has on the TJICF in tandem configuration numerically, using Large-eddy simulation (LES). The study was initially carried on both circular and elliptic SJICF numerically, to assess the capability of the proposed LES model. Steady Reynolds-Averaged Navier Stokes (RANS) models were carried out on both cases to provide an initialisation baseline for the LES model. Quantitative analysis conducted on the RANS show decent agreement with the experimental measurements. Near and far-field structures observed in the experimental flow visualisation are also reproduced by the LES model. The LES model is then used to predict both circular and low aspect ratio elliptic tandem TJICF and analysis is conducted based on the vorticial structures and jet trajectory. The front jet in both cases is observed to have shielded the rear jet against the crossflow. However, the extent of this shielding effect largely depends on the jet geometry. The counter-rotating vortex pairs of both jets produced were observed to eventually merge further downstream. Jet penetrations for both tandem TJICF are also observed to be much higher compared to their SJICF case.